Spanish Consensus Guidelines on prophylaxis with bypassing agents in patients with haemophilia and inhibitors - López-Fernández, Maria Fernanda; Roca, Carmen Altisent; Álvarez-Román, Maria Teresa; Canaro Hirnyk, Mariana Isabel; Mingot-Castellano, Maria Eva; Jiménez-Yuste, Víctor; Cid Haro, Ana Rosa; Pérez-Garrido, Rosario; Sedano Balbas, Carmen (Thrombosis and Haemostasis, 2016)
Prophylaxis with the blood clotting factor, factor VIII (FVIII) is ineffective for individuals with haemophilia A and high-titre inhibitors to FVIII. Prophylaxis with the FVIII bypassing agents activated prothrombin complex concentrates (aPCC; FEIBA® Baxalta) or recombinant activated factor VII (rFVIIa; Novo-Seven®, Novo Nordisk) may be an effective alternative. It was our aim to develop evidence -and expert opinion- based guidelines for prophylactic therapy for patients with high-titre inhibitors to FVIII. A panel of nine Spanish haematologists undertook a systematic review of the literature to develop consensusbased guidance. Particular consideration was given to prophylaxis in patients prior to undergoing immune tolerance induction (ITI) (a process of continued exposure to FVIII that can restore sensitivity for some patients), during the ITI period and for those not undergoing ITI or for whom ITI had failed. These guidelines offer guidance for clinicians in deciding which patients might benefit from prophylaxis with FVIII bypassing agents, the most appropriate agents in various clinical settings related to ITI, doses and dosing regimens and how best to monitor the efficacy of prophylaxis. The paper includes recommendations on when to interrupt or stop prophylaxis and special safety concerns during prophylaxis. These consensus guidelines offer the most comprehensive evaluation of the clinical evidence base to date and should be of considerable benefit to clinicians facing the challenge of managing patients with severe haemophilia A with high-titre FVIII inhibitors.
Keywords: Prophylaxis; bypassing agents; haemophilia; inhibitors; guidelines